1970
DOI: 10.3126/jpn.v1i2.5404
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mediastinal lesions: a study of 27 cases

Abstract: Teaching Hospital. All details of the patients pertinent clinical history was obtained from case record file in the department. Results:Out of 27 cases, 18 cases (66.6%) were benign and 7 (26%) were malignant and 2 (7.4%) were inconclusive. Among the malignant lesions, primary tumors constituted 71.5% of cases while metastases were 28.5%. Most of the lesions were seen in the anterior compartment followed by the posterior compartment. Age range was 4 months to 70 years with a mean age of 35.5 years. Thymoma (8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
26
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 3 publications
6
26
1
Order By: Relevance
“…sixth decade of life. Our study is in concordance with Karki S et al [10] who showed in a study of 27 cases with mediastinal lesions that 18…”
Section: Discussionsupporting
confidence: 93%
“…sixth decade of life. Our study is in concordance with Karki S et al [10] who showed in a study of 27 cases with mediastinal lesions that 18…”
Section: Discussionsupporting
confidence: 93%
“…The higher incidence of non-neoplastic patients is due to large number of patients diagnosed as 'suggestive of sarcoidosis' where they accounted for 43.4% of the patients. Karki and Chalise (2011) study findings agreed with our results where they observed a lower incidence of neoplastic patients. Similarly, Vaziri et al (2009) andPérez Dueñas et al (2010) reported that most of their patients were neoplastic, representing 60 and 78.6% of their patients, respectively.…”
Section: Discussionsupporting
confidence: 96%
“…The age range and mean ages are very close to study by Biswajit Dubashi et al and another study by Karki and Chalise. 7,8 In this study, 91.6% of patients are symptomatic at presentation with the most common symptom being cough (87.5%) followed by chest pain (81.5%) and dyspnoea (79.1%). This is in accordance from a study by Davis, et al and Shrivastava et al, in which 85% of the patients with malignant mediastinal tumours were symptomatic.…”
Section: Discussionmentioning
confidence: 63%